Evaluation Of Internet Of Things (Iot) For Monitoring And Control Of Home Electronic Appliances - Deri Sembiring (International Journal of Management, Economic and Accounting, 2023)
This research aims to evaluate the effectiveness and reliability of Internet of Things (IoT) technologies in the context of monitoring and control of household electronic appliances. Rapid developments in the IoT domain have opened up new opportunities to integrate home appliances into a connected digital ecosystem, with the aim of improving user efficiency, convenience, and security. The methodology of this research includes the implementation of an IoT infrastructure consisting of sensors, actuators, and communication platforms, as well as the development of control applications via mobile devices. Selected household electronic appliances, such as lighting devices, air conditioners, and security systems, will be integrated into the IoT network to facilitate remote monitoring and control. During the evaluation, performance parameters such as response time, connection reliability, and energy consumption will be measured and analyzed. In addition, user experience in using the control application via mobile devices will also be evaluated through questionnaires and interviews. The results of this study are expected to provide in-depth insights into the potential and limitations of IoT implementation for monitoring and control of household electronic appliances. The implications of the results of this study can support the development of better solutions in creating a smart, efficient, and customizable home environment according to individual preferences and needs.